Narrar Ã rua moderna: experiência que vem da Rússia czarista (Dialogos, 2016)
Resenha do livro:GÓGOL, Nikolai. Avenida Niévski. Trad. Rubens Figueiredo. São Paulo: Cosac Naify, 2013, v. I. 96 p.; v. II. 32 p., 30 ils.